Pengaruh Dark Pattern E-Commerce Terhadap Kepercayaan Dan Keputusan Pembelian Pengguna - Muhammad Yasyfi Alhafizh; Muhammad Naufal Aulia; Muhammad Fabio Usama; Mohammad Zaky Nauval; Vina Serevina (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2026)
The rapid expansion of e-commerce has led to the emergence of deceptive user interface strategies, commonly recognized as dark patterns, which coerce consumers into making unplanned digital actions. This research explores how these manipulative interfaces affect consumer trust and purchasing behavior within the Indonesian market. Utilizing a quantitative explanatory design, data were gathered from 100 active online shoppers selected via purposive sampling. The data evaluation was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to assess both measurement and structural pathways. The statistical outcomes indicate that encountering dark patterns substantially diminishes user trust, while simultaneously and directly provoking impulsive buying actions. Moreover, consumer trust functions as a partial mediator linking deceptive design elements to final transaction behaviors. These insights emphasize the critical necessity for transparent interface regulations and enhanced digital consumer protection frameworks in emerging economies.